2015
DOI: 10.1007/s00240-015-0805-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized comparison between superior calyceal access versus inferior calyceal access in PCNL for inferior calyceal stones with or without pelvic stones

Abstract: The objective of this study is to assess the efficacy of superior calyceal access versus inferior calyceal access for inferior calyceal calculi with or without pelvic calculi. A total of 100 patients with inferior calyceal calculi or inferior calyceal calculi with pelvic calculi were included in this prospective randomized study. In 50 patients (Group 1), a fluoroscopy-assisted superior calyceal puncture was made, and in other 50 patients (Group 2), access was obtained through a fluoroscopy-assisted inferior c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
2
8
1
Order By: Relevance
“…Stone free rates from isolated pelvic and lower calyceal calculi were significantly higher in superior calyceal group than inferior calyceal group. Overall, stone clearance rates are consistent with previous studies for superior calyceal access [2,9,13].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Stone free rates from isolated pelvic and lower calyceal calculi were significantly higher in superior calyceal group than inferior calyceal group. Overall, stone clearance rates are consistent with previous studies for superior calyceal access [2,9,13].…”
Section: Discussionsupporting
confidence: 89%
“…With the advent of miniaturized access tracts and thereby minimal postoperative complications, PCNL dominates the treatment modalities for larger sized and/or complex renal stone management [1]. One of the major advantages of PCNL over other techniques is the higher stone clearance [2]. A key requisite to a successful procedure is establishing an optimal direct and safe access to the intrarenal collecting system facilitating ease of intrarenal navigation resulting in complete stone clearance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the upper calyx access is more favorable for the treatment of complex lower pole stones than LCA [16]. Singh et al [23] compared the outcomes of LCA and the upper calyx access in the treatment of lower pole stones. A second puncture was needed in 10% of the patients in the LCA group while it was not needed in any patient in the upper calyx group.…”
Section: Discussionmentioning
confidence: 99%
“…While standardising for the experience level of the surgeon, variation in the institution-specific sophistication of instrumentation [24], and the difference in surgical approach (in terms of access tract location, tract size, and a number of punctures) [1,25].…”
Section: Introductionmentioning
confidence: 99%